REFORMASI TNI: ANALISA KOMANDO TERRITORIAL (KOTER) DALAM HUBUNGAN SIPIL-MILITER - Angela, Deni (Jurnal Polinter : Kajian Politik dan Hubungan Internasional, 2024)
This research purpose to provide an analysis of the existence of Koter in Indonesia, especially in responding to TNI’s internal reform commitments. However, reviews regarding to Koter always proceed stiffy and slowly due to internal approval from TNI itself. In fact, plans to add Koter are always carried out even civil approval is always present. Excistence of Koter is also of the cause of TNI reform which has not yet been completed. Meanwhile, the author uses an explanatory qualitative research method to answer problems regarding the existence of Koter. In several findings and analysis the existence of Koter is no longer relevant in the democracy era, firstly, it’s about existance often clashes with the duties of the Polri, it’s not in accordance with the principles of decentralization, especially in territorial functions which should be in the regional government programs make the TNI lose professionalism as soldier who should focus on defense and sovereignty. Existence of the koter is no longer relevant and returning the military to baracks an obligation to reform the TNI.